Fair Valuation and Risk Assessment of Dynamic Hybrid Products in Life Insurance: A Portfolio Consideration - Bohnert, Alexander; Gatzert, Nadine (Geneva Papers on Risk and Insurance-Issues and Practice, 2014)
Dynamic hybrid products are innovative life insurance products particularly offered in the German market and intended to meet new consumer needs regarding stability and upside potential. These products are characterised by a periodical rebalancing process between the policy reserves (i.e. the premium reserve stock), a guarantee fund and an equity fund. The policy reserve thereby corresponds to the one also valid for traditional participating life insurance products. Hence, funds of dynamic hybrids that are allocated to the policy reserves in times of adverse capital market environments earn the same policy interest rate determined for the participating life insurance policyholders and, hence, at least a guaranteed interest rate. In this paper, we study the fair valuation and risk situation of an insurer offering both dynamic hybrid and traditional participating life insurance contracts. The results reveal considerable interaction effects between the two contract types within the portfolio that strongly depend on the portfolio composition, thereby emphasising merits as well as risks associated with offering dynamic hybrids.
WiSo-Import:2015-03-26:4088
Keywords: Risk Assessment; Life insurance; Fair valuation; Dynamic Hybrid Products